ARTIFICIAL INTELLIGENCE TRENDS IN HUMAN RESOURCES MANAGEMENT : A SYSTEMATIC LITERATURE REVIEW: ARTIFICIAL INTELLIGENCE IN HUMAN RESOURCES MANAGEMENT - Sri Annisa; Ritha F. Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Advances in technology and the need for efficiency in human resource management have fuelled the application of artificial intelligence (AI) in the context of HR management. This literature review investigates the recent developments of AI in HR management, covering AI applications in recruitment, employee selection, training, performance evaluation, and employee welfare management. By delving into the relevant literature, this research identifies the trends, challenges, and benefits of applying AI in various aspects of HR management. The results of this review provide in-depth insights into the role of AI in improving efficiency, equity, and productivity in HR management, while illustrating the future direction of AI research and implementation in the context of HR management.